Forensic epidemiology - Freeman, Michael (Elsevier, 2016)
In Forensic Epidemiology, the authors present the legal and scientific theories underlying the methods by which risk is used in the investigation of individual causation. Methods and principles from epidemiology are combined with those from a multitude of other disciplines, including general medicine, pharmacology, forensic pathology, biostatistics, and biomechanics, inter alia, as a basis for investigating the plausibility of injury and disease exposures and mechanisms. The ultimate determination of the probability of causation (PC) results from an assessment of the strength of association of the investigated relationship in the individual, based on a comparison between the risk of disease or injury from the investigated exposure versus the risk of the same disease or injury occurring at the same point in time in the individual, but absent the exposure. The principles and methods described in Forensic Epidemiology will be of interest to those who work and study in the fields of forensic medicine, epidemiology, and the law